Existence for Singular Periodic Problems: A Survey of Recent Results - Jifeng Chu; Juntao Sun; Patricia J. Y. Wong (Abstract and Applied Analysis)
We present a survey on the existence of periodic solutions of singular differential equations. In particular, we pay our attention to singular scalar differential equations, singular damped differential equations, singular impulsive differential equations, and singular differential systems.